Prison Violence as Punishment - Bell, William L. (Ethical theory and moral practice, 2024)
The United States carceral system, as currently designed and implemented, is widely considered to be an immoral and inhumane system of criminal punishment. There are a number of pressing issues related to this topic, but in this essay, I will focus upon the problem of prison violence. Inadequate supervision has resulted in unsafe prison conditions where inmates are regularly threatened with rape, assault, and other forms of physical violence. Such callous disregard and exposure to unreasonable risk constitutes a severe violation of the rights of prisoners by the state. While there have been numerous legal, political, and activist efforts to draw attention to this issue—with the goal of reforming and making prisons safer—my goal is different. I argue that inmates who are victims of prison violence should have their sentences automatically reduced. Two distinct arguments are advanced in support of this claim. First, I argue that acts of prison violence are a sort of state-mediated harm which can thus be appropriately described as punishment-constituting. Second, and more straightforwardly, I argue that the compensation owed to prisoners who are victims of prison violence may naturally take the form of a reduced sentence.